THE BEST SMART RESEARCH: INTELLIGENCE SHAPING THE FUTURE OF MEDICINE - Zokirjonova Havasxon Mahammadjon qizi; Tursunmetov Ibodulla Roʻzibayevich (TADQIQOTLAR, 2025)
This article highlights the most relevant and advanced smart research in 21st-century medicine. It analyzes innovations in healthcare through artificial intelligence (AI), smart medical devices, genomics, neurotechnologies, and modern technologies applied  in  medical  education.  The  article  presents  positive  changes  such  as  early disease detection, the creation of personalized treatment plans, and new opportunities for paralyzed patients using AI. It also predicts the role of smart clinics and robotic surgeons  in  the  future.  These  advancements  bring  great  opportunities  and responsibilities for modern physicians.